Synthesis and characterization of a hydrogel film based on chitosan/carboxymethyl cellulose for food packaging applications - Saba Sabzevari; Hasan Farrokhzad; Ali Poorkhalil (Carbohydrate Polymer Technologies and Applications)
This study focuses on the synthesis of a novel hydrogel film composed of chitosan (CS) and carboxymethyl cellulose (CMC) crosslinked with citric acid (CA). The primary objective is to enhance the mechanical, thermal, and hydrophobic properties of CMC and CS by optimizing the crosslinking density through varying CA concentration. Glycerin was added as a plasticizer in selected formulations. Hydrogel films were synthesized using equal volumes of CS and CMC solutions with different amounts of CA (12, 18, and 24 wt.%) at 80°C. The films were characterized by water vapor permeability (WVP), contact angle, solubility, swelling behavior, mechanical properties, and thermal performance. The optimized formulation (18 wt.% CA) exhibited WVP of 7.68 × 10−9 g h−1 m−1 Pa−1 and a contact angle of 45.19 °, indicating improved moisture barrier and hydrophobicity. Tensile strength, Young's modulus, and elongation at break were 7.12 MPa, 0.22 MPa, and 35.95 %, respectively. Thermal analysis indicated an onset degradation temperature of 255°C and a maximum degradation temperature of 294.1°C. These findings suggest that CA-crosslinked CS-CMC hydrogel films possess a balanced combination of mechanical robustness, thermal stability, and moisture barrier performance, making them promising candidates for applications in food packaging, biomedical devices, and environmentally sustainable coatings.